SISTEM PAKAR UNTUK MENENTUKAN SANKSI PELANGGAR LALU LINTAS SEPEDA MOTOR DAN MOBIL MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Agus Budiantoro; Atiqah Meutia Hilda; E. Rizal (Prosiding Seminar Nasional Teknoka, 2019)
Nowadays, to determine the ticketed sanctions in court still using experts without systematic assistance. Certainly, it is very unfortunate if the technology is not utilized in this field. A similar problem also exists with the traffic police on duty to do out the crossing and socialize the articles and fines that apply to traffic violators. The police must also memorize the articles of traffic violations, but only those that are often violated by drivers because there are many articles on traffic violations that the police cannot memorize. Therefore, in this research, the writer creates a system to assist judges in determining sanctions or fines for traffic violators, to assist the police in socializing the traffic violator, and to assist the drivers in knowing the rules, and also the traffic articles. The Forward Chaining method would be more suitable to be used for those systems because the research field uses facts to be sure. The objects of this research are car and motorcycle riders. The existence of several case examples are used by the writer that is useful to test the accuracy of the process or the results of this consultation, researchers also provide examples to the drivers, the police, and also legal experts for testing this traffic expert system. With the level of validation of truth that has been achieved, this traffic expert system can be used as a method of judges, violators or police in determining ticketing sanctions